Ethical Indigenous Economies - Kelly, Dara; Woods, Christine (Engaged Scholar Journal, 2021)
In this article, the authors argue that trans-systemic knowledge system analysis of Indigenous-to-Indigenous economics enables generative thinking toward Indigenous futures of economic freedom. The authors apply a trans-systemic lens to critically analyze persistent development philosophy that acts as a barrier to the advancement of Indigenous economic development thinking. By exploring ways in which colonial discourse entraps Indigenous nations within circular logic in service of a normative centre the need for new economic logic is apparent. Shifting to trans-systemic knowledge systems analysis to include diverse insights from Māori and other Indigenous economic philosophy, the authors show that it is not profit and financial growth that matters in and of itself. Rather, according to Indigenous definitions of wealth, economic freedom and development are constituted by value creation that aligns with Indigenous worldviews and principles. Indigenous economic knowledge centred on relationship, reciprocity and interconnectedness fosters Indigenous economic freedom.